Will the Norwegian pension reform reach its goals? An integrated micro-macro assessment - Erling Holmøy; Kyrre Stensnes (Statistics Norway, Research Department, 2008)
The Norwegian pension reform of 2006 intends to (1) improve long run fiscal sustainability by reducing the growth in public old-age expenditures, (2) strengthen labour supply incentives, and (3) maintain the main redistributive features of the present system. We assess to what extent the reform is likely to achieve these three goals, using two empirical models iteratively: We combine a detailed dynamic micro simulation of individual benefits and government pension expenditures with a CGE-model, which captures behavioural effects and equilibrium repercussions. We find that the pension reform improves fiscal balances substantially. Compared to a no-reform scenario, the payroll tax rate can be cut by 10 percentage points in 2050. Increased employment contributes more to the fiscal improvement than the reduction in pension expenditures. However, these changes are basically level effects; the reform has a surprisingly small effect on the growth rate of the necessary tax burden starting in 2020. In particular, the growth rate of public pension expenditures is hardly affected. Stronger government finances and higher employment is obtained at the expense of a significant increase income inequality among old age pensioners.
Keywords: H30; H55; H62; H68; O15; 330; Pension reforms; Fiscal sustainability; Income distribution; Computable general equilibrium model; Dynamic micro simulation